Measurement of airway function using invasive and non-invasive methods in mild and severe models for allergic airway inflammation in mice - Verheijden, Kim A. T.; Henricks, Paul A. J.; Redegeld, Frank A.; Garssen, Johan; Folkerts, Gert (Frontiers in Pharmacology, 2014)
In this study a direct comparison was made between non-invasive and non-ventilated unrestrained whole body plethysmography (Penh) (conscious animals) and the invasive ventilated lung resistance (RL) method (anaesthetized animals) in both mild and severe allergic airway inflammation models. Mild inflammation was induced by intraperitoneal sensitization and aerosols of ovalbumin. Severe inflammation was induced by intraperitoneal sensitization using trinitrophenyl-ovalbumin, followed by intranasal challenges with IgE-allergen complexes. A significant increase in airway responsiveness to methacholine was observed in the mild inflammation group when RL was measured. Significant changes in both RL and Penh were observed in the severe inflammation groups. There was a significant increase in the number of inflammatory cells in the Broncho-Alveolar Lavage Fluid (BALF) in both the mild and severe inflammation animals. The enforced ventilation of the animals during the RL measurement further increased the number of cells in the BALF. IL-2 and RANTES levels in the BALF were higher in the severe inflammation groups compared to the mild inflammation groups. Penh gave only reliable measurements during severe airway inflammation. Measuring RL gave consistent results in both mild and severe allergic airway inflammation models however, ventilation induced an additional cell influx into the airways.